Microsatellite based genetic diversity estimation in Sikkim Singharey goat population - SHIVAHRE, PUSHP RAJ; VERMA, N K; AGGARWAL, RAK; SHARMA, REKHA; DANGI, P S; BHUTIA, N T; AHLAWAT, SONIKA (The Indian Journal of Animal Sciences, 2017)
Singharey goats of Sikkim is a lesser known population of goat. The study was undertaken to know the genetic diversity occurring in these goats. Alleles (182) were observed across the microsatellite loci. The average observed and effective numbers of alleles were 7.913 ± 0.576 and 3.496 ± 0.328, respectively. A polymorphic information content (PIC) value varied from 0.311 to 0.945 with an overall mean of 0.661 ± 0.036. Mean observed (HO) and expected (He) heterozygosities were 0.507 ± 0.042 and 0.649 ± 0.034, respectively. The inbreeding estimate (FIS) was 0.225 ± 0.046 indicated moderate level of inbreeding. The population was stable with respect to size and was non- bottlenecked. The observed normal L-shaped curve indicated no mode shift in the population.